2020
DOI: 10.1016/j.jpha.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for PET imaging of the receptor for advanced glycation endproducts (RAGE)

Abstract: The implication of the receptor for advanced glycation end-products (RAGE) in numerous diseases and neurodegenerative disorders makes it interesting both as a therapeutic target and as an inflammatory biomarker. In the context of investigating RAGE as a biomarker, there is interest in developing radiotracers that will enable quantification of RAGE using positron emission tomography (PET) imaging. We have synthesized potential small molecule radiotracers for both the intracellular ([ 18 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…In the present study, we did not confirm the involvement of RAGE using knockout or knockdown experiments. High concentration of FPS-ZM1 at 10 μM has inhibitory effect on androgen receptor, benzodiazepine receptor, kappa opioid receptor and melatonin receptor [ 55 ]. However, none of these receptors bind to AGEs.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we did not confirm the involvement of RAGE using knockout or knockdown experiments. High concentration of FPS-ZM1 at 10 μM has inhibitory effect on androgen receptor, benzodiazepine receptor, kappa opioid receptor and melatonin receptor [ 55 ]. However, none of these receptors bind to AGEs.…”
Section: Discussionmentioning
confidence: 99%
“…In the early pathological studies of AD, it has been reported that RAGE is highly expressed in the brain lesions and upregulated with the progression of the disease (Kong et al, 2020). In addition, this target has been used to develop PET probes for imaging AD disease progression (Drake et al, 2020). Therefore, targeting RAGE for drug delivery can realize the specific accumulation of the delivery system in the lesion.…”
Section: Bbb Alteration-based Brain-targeting Delivery Strategies: Pr...mentioning
confidence: 99%
“…Most recently, [ 18 F]95 ([ 18 F]InRAGER) was reported as a selective PET ligand for flRAGE (K d = 1 nM), which was achieved via an isotopic exchange with [ 18 F]KF. 97 Although a high initial brain uptake (SUV max = ca. 2.0) was observed in rats, the development of new radiosynthetic methods is necessary to address poor radiochemical yield and low molar activity.…”
Section: Pet Probes For Colony Stimulating Factormentioning
confidence: 99%
“…Subsequently, [ 11 C]­FPS-ZM1 was successfully synthesized by palladium-catalyzed carbonylation with [ 11 C]­CO. , However, a high nonspecific binding was observed for [ 11 C] 94 ([ 11 C]­FPS-ZM1) in both wild-type and AD mice by in vitro autoradiography experiments, which was possibly attributed to its high lipophilicity (cLogP = 5.25). Most recently, [ 18 F] 95 ([ 18 F]­InRAGER) was reported as a selective PET ligand for flRAGE ( K d = 1 nM), which was achieved via an isotopic exchange with [ 18 F]­KF . Although a high initial brain uptake (SUV max = ca.…”
Section: Emerging Biological Targets In Neuroinflammatory Processes F...mentioning
confidence: 99%